Do you like me when the sun is shining? The influence of weather and point-in-time on the stakeholder-Dialogue in Facebook. Issue 3 (5th April 2021) - Martin, Sebastian; Wetzelhütter, Daniela; Grüb, Birgit
Abstract : Purpose: The purpose of this paper is to investigate the influence of external factors on the Facebook dialogue. As both weather and point in time substantially. As both weather and point in time substantially influence people's lives, it can be assumed that both factors may also affect communication on Facebook. To the best of the authors' knowledge, this is the first study focusing on the impact of the external factors "weather" and "point in time" on a public utility's Facebook communication. Design/methodology/approach: The potential influence is explored through the case study of an Austrian public utility. The study focuses on 321 postings, published via the company's official Facebook account between August 2016 and February 2018. Findings: The empirical results confirm the influence of "weather" and "point in time" indicators on the stakeholder dialogue. The findings highlight how the relevant items affect the posting behavior of a utility, as well as stakeholders' reactions, comments and shares. Originality/value: By introducing both external factors to the social media literature, this paper broadens the understanding of Facebook communications beyond the sender and receiver of digital information. In this way, the research contributes to a more holistic view of Facebook dialogue. It provides practical advice on how social media managers of public utilities may use weather forecasts and "point in time" considerations to more strategically foster stakeholder dialogue in social media.